(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background. Physical activity has been proven effective in improving and maintaining the health of the elderly. But the participation of the elderly in physical activity is not proportional to the number of elderly in the community. This is due to physical activity only meeting physical health, while other elderly needs such as social, psychological and environmental are not met. Interventions are needed to maintain sustainable physical activity that can improve the quality of life of the elderly. Aim. This study aimed to determine the effects of psychoeducation and physical exercise for the elderly programs with local wisdom approach to quality of life of the elderly in the community. Method. This research method used a Quasi-Experiment Pre-Post Test Design with Control Group. The sample of this study was 132 elderly who lived in rural and urban areas, using Multistage Random Sampling techniques. Data analysis used correlation pearson (rho), t test and multivariate analysis (regresi linier). Results. The effect of program can improve the function of physical activity and quality of life of elderly. Meanwhile the factors that affect the quality of life of the elderly are education, mental status, function of physical activity and intentions. Conclusion. This Program affects the function of physical activity and quality of life of the elderly in the community. Determinants of quality of life can be used as a basic for developing health care programs for the elderly.